Vanillin and vanillic acid modulate antioxidant defense system via amelioration of metabolic complications linked to Fe2+-induced brain tissues damage - Salau, Veronica F.; Erukainure, Ochuko L.; Ibeji, Collins U.; Olasehinde, Tosin A.; Koorbanally, Neil A.; Islam, Md. Shahidul (Metabolic brain disease, 2020)
The therapeutic effect of phenolics on neurodegenerative diseases has been attributed to their potent antioxidant properties. In the present study, the neuroprotective activities of vanillin and vanillic acid were investigated in Fe 2+ - induced oxidative toxicity in brain tissues by investigating their therapeutic effects on oxidative imbalance, cholinergic and nucleotide-hydrolyzing enzymes activities, dysregulated metabolic pathways. Their cytotoxicity was investigated in hippocampal neuronal cell lines (HT22). The reduced glutathione level, SOD and catalase activities were ameliorated in tissues treated with the phenolics, with concomitant depletion of malondialdehyde and nitric oxide levels. They inhibited acetylcholinesterase and butyrylcholinesterase activities, while concomitantly elevated ATPase activity. Treatment with vanillin led to restoration of oxidative-depleted metabolites and reactivation of the pentose phosphate and purine metabolism pathways, with concomitant activation of pathways for histidine and selenoamino metabolisms. While vanillic acid restored and reactivated oxidative-depleted metabolites and pathways but did not activate any additional pathway. Both phenolics portrayed good binding affinity for catalase, with vanillic acid having the higher binding energy of −7.0 kcal/mol. Both phenolics were not cytotoxic on HT22 cells, and their toxicity class were predicted to be 4. Only vanillin was predicted to be permeable across the blood brain barrier (BBB). These results insinuate that vanillin and vanillic acid confer a neuroprotective effect on oxidative brain damage, when vanillin being the most potent.